Sistem Informasi Penilaian Kinerja Karyawan Metode Umpan Balik 360 Derajat - Kusdinar, Dandi Agih; Meiyanti, Ruci; Jumaryadi, Yuwan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
ITS is a company engaged in the construction sector and routinely conducts employee performance assessments. However, the current assessment process is still subjective because it is only carried out by superiors without the involvement of other parties and without clear assessment criteria to support decision-making. This study aims to develop a web-based employee performance assessment information system by implementing the 360 ​​Degree Feedback method, which allows for comprehensive evaluations from various perspectives, including superiors, coworkers, and subordinates. The system development process uses the Waterfall method, which includes the stages of needs analysis, design, implementation, and testing. Problem analysis is carried out using the Fishbone method to identify the main causes of the ineffectiveness of the previous system. The system design is depicted through UML diagrams, while application development uses the Yii Framework and MySQL database. Functional testing of the system is carried out using the Black Box Testing method to ensure each feature runs as expected. The results of this study are a web-based employee performance assessment information system that assesses based on three main criteria: discipline, technical skills, and personality, resulting in a more objective, accurate, and comprehensive assessment.